Improving Students' Social Skills Through Project-Based Learning Class V Students Of Muhammadiyah 24 Surabaya Primary School - Izza, Roisyatul; Tjipto Subroto, Waspodo; Jacky, M.; Sukartiningsih, Wahyu; Istiqfaroh, Nurul; Setyaningrum , Norma (The Indonesian Journal of Social Studies, 2023)
Project-based learning is learning with long-term activities that involve students in designing, creating, and displaying products to solve real-world problems. Project-based learning is based on previous theories and then referred to as a form of project-based learning construct. This research was conducted to improve students' social skills through project-based learning. This research, based on interviews and observations of class 5 at SD Muhammadiyah 24 Surabaya, found that students' social skills were still low. This research aimed to improve children's social skills by using models of project-based learning. The research method used is Kurt Lewin's Class Action Research (PTK) model. The research subjects were 24 fifth-grade students at SD Muhammadiyah 24 Surabaya. This research was carried out through pre-intervention stages, cycle I and cycle II. Data analysis techniques are qualitative and quantitative data analysis. The results of the research show that there is an increase in students' social skills, namely the ability to take turns or share, the ability to appreciate or respect, the ability to help or assist, the ability to follow instructions, the ability to control emotions, the ability to convey opinions, the ability to accept opinions obtained from data up to cycle II and obtain the increase in the average value was 45. Based on the research results, it can be concluded that the modelproject based learning can improve students' social skills.